Determination of Methomyl Residue in Tobacco Samples by Heart-Cutting Two-Dimensional Liquid Chromatography with Tandem Mass Spectrometry - Shihao Shen; Min Chen; Tiannan Wang; Ting Fei; Dianhai Yang; Miaoling Cao; Da Wu (International Journal of Analytical Chemistry)
A novel heart-cutting two-dimensional liquid chromatography coupled with tandem mass spectrometry (2D-LC-MS/MS) was developed for the qualitative and quantitative analysis of methomyl residue in tobacco. Compared to traditional methodologies, fairly high sensitivity and stability were achieved, and the sample procedure was simplified in the two-dimensional liquid chromatography (2D-LC) method. Although methomyl had poor retention performance in most of the reversed-phase liquid chromatography (RPLC) columns, an effective RP/RP strategy was successfully facilitated. An XB-Phenyl column was employed in the first dimension to effectively remove thousands of interference compounds in the matrix. In the second dimension, an ADME column was applied for further separation. After optimization of the separation conditions, a six-way valve was utilized for direct transformation of the target fraction from the 1st column to the 2nd column. A dynamic range of 2.5 ng/mL to 500 ng/mL was achieved with correlation coefficient (r2) greater than 0.9995. The limit of detection and limit of quantification were determined to be 0.69 and 2.30 ng/mL, respectively. The 2D-LC method shows high sensitivity, good reproducibility, and recovery for methomyl in tobacco samples. Therefore, the new method was quite suitable for routine analysis.